Role of preoperative magnetic resonance imaging on the surgical outcomes of radical prostatectomy: Does preoperative tumor recognition reduce the positive surgical margin in a specific location? Experience from a Thailand prostate cancer specialized center - Thitipat Hansomwong; Pat Saksirisampant; Sudhir Isharwal; Pubordee Aussavavirojekul; Varat Woranisarakul; Siros Jitpraphai; Sunai Leewansangtong; Tawatchai Taweemonkongsap; Sittiporn Srinualnad (Asian Journal of Urology)
Objective: Multiparametric magnetic resonance imaging (MRI) has become the standard of care for the diagnosis of prostate cancer patients. This study aimed to evaluate the influence of preoperative MRI on the positive surgical margin (PSM) rates. Methods: We retrospectively reviewed 1070 prostate cancer patients treated with radical prostatectomy (RP) at Siriraj Hospital between January 2013 and September 2019. PSM rates were compared between those with and without preoperative MRI. PSM locations were analyzed. Results: In total, 322 (30.1%) patients underwent MRI before RP. PSM most frequently occurred at the apex (33.2%), followed by posterior (13.5%), bladder neck (12.7%), anterior (10.7%), posterolateral (9.9%), and lateral (2.3%) positions. In preoperative MRI, PSM was significantly lowered at the posterior surface (9.0% vs. 15.4%, p=0.01) and in the subgroup of urologists with less than 100 RP experiences (32% vs. 51%, odds ratio=0.51, p<0.05). Blood loss was also significantly decreased when a preoperative image was obtained (200 mL vs. 250 mL, p=0.02). Multivariate analysis revealed that only preoperative MRI status was associated with overall PSM and PSM at the prostatic apex. Neither the surgical approach, the neurovascular bundle sparing technique, nor the perioperative blood loss was associated with PSM. Conclusion: MRI is associated with less overall PSM, PSM at apex, and blood loss during RP. Additionally, preoperative MRI has shown promise in lowering the PSM rate among urologists who are in the early stages of performing RP.